Investigation of the impact of different ARC layers using PC1D simulation: application to crystalline silicon solar cells - Galib Hashmi; Mohammad Junaebur Rashid; Zahid Hasan Mahmood; Mahbubul Hoq; Md. Habibur Rahman (Journal of Theoretical and Applied Physics)
Abstract In this work, the impact of six different anti-reflection coating (ARC) layers has been investigated using PC1D simulation software. Simulation shows that the range of 500–700 nm would be suitable for designing an ARC. Designing a single-layer silicon nitride (Si3N4) ARC for 600 nm wavelength and with a thickness of 74.257 nm, a silicon solar cell with 20.35% efficiency has been simulated. Very closely followed by a 20.34% efficient silicon solar cell with 74.87 nm thick zinc oxide (ZnO) ARC layer. Significant increase in efficiency has been observed by applying ARC in respect to not applying any kind of ARC. After efficient solar cell modeling, optimum efficiency of 20.67% is being achieved by using SiO2 surface passivation and Si3N4 ARC layer. The effects on voltage, current, photovoltaic efficiency, reflectivity and external quantum efficiency due to ARCs are also represented in this work.